Reporting of ethical considerations in clinical trials in Chinese nursing journals. (June 2019) - Wu, Yanni; Howarth, Michelle; Zhou, Chunlan; Ji, Xue; Ou, Jiexia; Li, Xiaojin
Background: It is acknowledged that publishers now require all primary research papers to demonstrate that they have obtained ethical approval for their research. Objectives: To assess the rate of reporting of ethical approval in clinical trials in core nursing journals in mainland China. Research design: A retrospective observational study. Participants: All clinical trials published in all of the 12 core nursing periodicals from 2016 edition China Science and Technology Journal Citation Report (core version) between 2013 and 2016 were retrieved by hand to explicate rate of reporting ethical approval and informed consent. Ethical considerations: The study did not require approval from the research ethics committee as it did not involve human subjects or records. Results: In total, 40, 278 papers were published in 12 nursing periodicals between 2013 and 2016. Out of these, 9488 (23.6%) focused on clinical trials. Informed consent obtained from patients or the legally authorized representative was reported in 51.8% of clinical trials. Notably, only 27.4% of clinical trials reported that they had obtained written consent. Furthermore, 25.9% of clinical trials described ethical approval; however, the rate of reporting informed consent and ethical approval in these 12 nursing journals in China during 4 years from 2013 to 2016 improved markedly, with 38.1%, 44.0%, 59.0% and 66.6%, respectively ( p < 0.001), and 17.6%, 21.9%, 28.6% and 35.8%, respectively ( p < 0.001). In addition, both reporting informed consent and reporting written informed consent had a positive significant correlation with the reporting ethical approval ( p < 0.05 or < 0.01). Conclusion: Chinese scientific nursing journals have improved the rate of reporting informed consent and ethical approval in clinical trials during the last 4 years. However, it should be noted that nearly half of clinical trials still did not report either ethical approval or whether informed consent was obtained. Efforts from editors, researchers, sponsors and authors are needed to ensure the transparency of ethical scrutiny and adherence to ethical guidelines in publishing clinical trials in Chinese nursing journals.